2018
DOI: 10.5698/1535-7597.18.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Practice guideline update summary: Efficacy and tolerability of the new antiepileptic drugs II: Treatment-resistant epilepsy

Abstract: To update the 2004 American Academy of Neurology (AAN) guideline for managing treatment-resistant (TR) epilepsy with second- and third-generation antiepileptic drugs (AEDs). 2004 criteria were used to systematically review literature (January 2003 to November 2015), classify pertinent studies according to the therapeutic rating scheme, and link recommendations to evidence strength. Forty-two articles were included. The following are established as effective to reduce seizure frequency (Level A): immediate-rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 53 publications
(63 reference statements)
0
17
0
Order By: Relevance
“… 26 According to the AES/AAN guideline, LTG (Level B) should and GBP (Level C) may be considered in patients aged ≥60 years with new-onset focal epilepsy. 27 A randomized, double-blind trial showed that the seizure-freedom rate did not differ significantly among CBZ, LTG, and LEV treatments. 35 In the Keppra vs.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 According to the AES/AAN guideline, LTG (Level B) should and GBP (Level C) may be considered in patients aged ≥60 years with new-onset focal epilepsy. 27 A randomized, double-blind trial showed that the seizure-freedom rate did not differ significantly among CBZ, LTG, and LEV treatments. 35 In the Keppra vs.…”
Section: Managementmentioning
confidence: 99%
“…The International League Against Epilepsy (ILAE) and the American Epilepsy Society/American Academy of Neurology (AES/AAN) recommended lamotrigine (LTG) and gabapentin (GBP) as efficacious monotherapies for newly diagnosed and untreated focal seizures based on strong evidence ( Table 1 ). 26 27 However, there are no guidelines for elderly patients with other types of seizures. Elderly patients are sensitive to the adverse effects of AEDs, and drug compliance in this population is affected more by the adverse effects of AEDs than by their efficacy.…”
Section: Managementmentioning
confidence: 99%
“…Before choosing a third-line medication, it's recommended to consult with a center specializing in epilepsy to verify diagnosis, consider a different combination of AEDs, or consider other non-pharmacological treatments, including neurosurgical treatment. Allocation of the AED to first, second and third line was based on a review of the relevant latest literature on different treatment strategies, level of evidence for AEDs efficacy, international guidelines (Kanner et al, 2018a;2018b), drug status in Poland (registration, availability and reimbursement) and clinical and daily use experience. Each member of the appointed group of experts expressed his/her comments, and after reaching a consensus, recommendations were made.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale of recommendation of AEDs use was strongly based upon results of recent guidelines in particular prepared by the Sub-Commission of the American Academy of Neurology (AAN) and the American Epilepsy Society (AES) (Kanner et al, 2018a(Kanner et al, , 2018b. Based on the clinical trial methodology, AAN experts identified three categories of recommendation strength (levels A, B and C) for monotherapy in new-onset epi-Joanna Jędrzejczak et al lepsy and add-on therapy in refractory epilepsy.…”
Section: Update Of International Treatment Guidelines In Focal Epilepmentioning
confidence: 99%
“…According to The Report of the American Epilepsy Society and the Guideline Development as a result of Class I studies, levetiracetam is effective as add-on therapy for treatment of resistant generalize epilepsy with generalize tonic clonic seizures and also addon therapy for treatment of juvenile myoclonic epilepsy and juvenile absence seizures [17] . It has been known that levetiracetam binds the synaptic vesicle protein 2A [18] , the activity of which is related to the exocytosis of transmitter vesicles [19,20] .…”
Section: Introductionmentioning
confidence: 99%